Currencies and the Allocation of Risk: The Welfare Effects of a Monetary Union - Neumeyer, Pablo Andrés (American Economic Review, 1998)
In a general equilibrium model with incomplete asset markets, nominal securities, and mean-variance preferences, a monetary union is desirable when the gain from eliminating excess volatility of nominal variables exceeds the cost of reducing the number of currencies with which to hedge risks.